2021
DOI: 10.3390/brainsci11121580
|View full text |Cite
|
Sign up to set email alerts
|

Altered Structural Covariance of Insula, Cerebellum and Prefrontal Cortex Is Associated with Somatic Symptom Levels in Irritable Bowel Syndrome (IBS)

Abstract: Somatization, defined as the presence of multiple somatic symptoms, frequently occurs in irritable bowel syndrome (IBS) and may constitute the clinical manifestation of a neurobiological sensitization process. Brain imaging data was acquired with T1 weighted 3 tesla MRI, and gray matter morphometry were analyzed using FreeSurfer. We investigated differences in networks of structural covariance, based on graph analysis, between regional gray matter volumes in IBS-related brain regions between IBS patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…The GSRS questionnaire is based on a 7‐level Likert scale, 1–7 recording the intensity and frequency of GI symptoms experienced during the previous 7 days. A higher score corresponds to a more severe symptom complained by the patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GSRS questionnaire is based on a 7‐level Likert scale, 1–7 recording the intensity and frequency of GI symptoms experienced during the previous 7 days. A higher score corresponds to a more severe symptom complained by the patients.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Somatization, defined as reporting physical bodily complaints without a known medical cause, is a psychological condition that may co-exist with IBS and is associated with impaired quality of life (QoL). 4 Although studies have investigated the relationship between somatization and IBS, 5,6 there is little information on the pathophysiological mechanism underlying this relationship. We recently showed that IBS-D patients with high somatization scores suffered significantly more severe GI symptoms than patients without somatization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sheehan et al ( 2011 ) found a correlation between the activity of the cingulate gyrus and the pain-related cerebral cortex in patients with IBS and the clinical symptoms of IBS. Increased neuronal activity has been reported in the medial prefrontal cortex, the insula, and the anterior cingulate gyrus, which are brain regions associated with visceral pain in patients with IBS (Grinsvall et al, 2021 ), and a larger area of excitation was observed in brain regions associated with nociceptive processing (e.g., the prefrontal cortex, the anterior cingulate gyrus, the thalamus, etc.,) (Seminowicz et al, 2010 ). Similarly, in a cohort study, the IBS group exhibited extensive structural changes in the brain compared with that in the controls, and these changes in the brain included a reduction or increase in gray matter volume in multiple regions of the sensorimotor, central executive, and default mode networks, and these changes were strongly associated with chronic visceral pain (Öhlmann et al, 2021 ).…”
Section: Abnormal Neural Signal Regulationmentioning
confidence: 99%
“…IBS is strongly associated with a high level of somatization and psychosocial morbidities [ 71 , 72 , 119 ]. In magnetic resonance imaging (MRI) experiments, Grinsvall et al [ 120 ] found that somatization level was associated with differences in local grey matter covariance, mainly in regions of the prefrontal cortex, insula, and cerebellum in IBS. The authors proposed that prefrontal mechanisms may be more important than insular mechanisms in the neurobiological sensitization process associated with IBS high somatization.…”
Section: Ibs: Structural and Functional Brain Changesmentioning
confidence: 99%